"You are beautiful, there is no doubt…" - Bagina, Elena (project baikal, 2014)
Hagia Sophia in Istanbul is a great grandmother of all Christian temples. The Muslim period of its history brought a lot of architectural additions and alterations. But none of the latest changes has come close to the highest standards of Byzantine architects.